Transforming Business Education: 21st Century Sustainable MBA Programs - Sroufe, Robert (Archīum Ateneo, 2021)
Business education should give students the skills to solve complex global challenges. It should align management practices with goals for a sustainable future. Sadly, few management schools even discuss the real issues business leaders face today. This article challenges others to develop a curriculum that embeds sustainability in the core of their programs. The authors argue that faculty and business school leadership should move beyond “saddlebag” initiatives that bolt sustainability onto the traditional, shareholder primacy-driven core. This article profiles three programs as case studies transforming business education to prepare leaders to achieve a more sustainable world. Business schools are torn between competing paradigms. Given the existential challenges facing humanity, business schools will have to change or simply lose relevancy. Our stories of disruption give evidence of success and hope for the coming transformation of business education and of capitalism itself. The lessons learned and insights in this article provide guidance for business school leaders aspiring to redefine management for global sustainability and business school programs. It is an open invitation for others to disrupt and rethink business education before it is too late.